Caracterização microestrutural e mecânica da liga de alta entropia CrMnFeCoNi conformada por laminação - Gustavo Henrique Sousa (2019)
High-entropy alloys (HEAs) are defined as alloys that normally contain five or more major elements in atomic fractions ranging from 5% to 35%. Despite the presence of a large number of components, HEAs often show rather simple crystal structures such as faces centered cubic (FCC). The distinctive feature of these alloys was originally attributed to the high configurational entropy associated with the mixing of a large number of constituents, allowing the formation of simple solid solutions. Since then, this new class of alloys has been extensively studied, and has attracted attention from academia, being reported with many interesting properties. In some cases the properties may be considerably better than those found in traditional materials, such as: good wear resistance, high temperatures resistance, high hardness, good thermal stability, good fatigue resistance characteristics and good corrosion resistance. Research for potential applications of high entropy alloys are using thermomechanical processing involving high deformation levels to refine the microstructure of these alloys and, cold rolling has been shown to be the main technology to improve the strength of these alloys. From this context, this work reports the effects of cold rolling on the final microstructure and the mechanical properties of a CrMnFeCoNi HEA processed by spray-formed and deformed to 30, 50, 90 and 146% of true strain. The results presented an alloy with excellent workability and exhibited a large work hardening capacity in cold rolling. The sample in as-sprayed condition is texture free and during cold rolled, the samples indicated a formation of {220} type texture. During cold rolling occurred the typical dislocation interactions dislocation-dislocation and the other from dislocation-mechanical twin boundary interactions, with the twinning contributing significantly to strain hardening because of the extra boundaries introduced during twinning (i.e., the dynamic Hall-Petch effect). The LAE CrMnFeCoNi in as-spray condition showed good results in terms of yield strength, tensile strength and elongation, about 319,0 MPa, 671,7 MPa and 43,6% respectively. The true strain sample of 146%, on the other hand, presented high tensile strength and yield strength, about 1256 MPa, at the cost of ductility.